THE GENOTYPES' FEED-BACK TO THE ENVIRONMENTAL FACTORS - Eugeniu ALEXANDROV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study aimed to analyze the complex relations between the anthropic factor and natural potential of Bistrita-Nasaud County, with relevance for the turistic phenomenon. Therefore, we proceed to an inventory of potential, based on visits and bibliographic source of information. Also,the study tries a description of adminitrative units, based on their potential, natural and anthropic, and also to identify typologies of villages, based on their turistic potential. The analize relives that the county has an abundance of natural and anthropic resources, such as: national parks, protected areas, spectacular lakes, unique caves in Europe, thermal water, traditions preserved thousands years, special culinary dishes. Therefore, a plenty of tourism activities are suitable in this region, including also special tourism such as hunting, equestrian, cultural tourism, rural tourism and agrotourism.